(untitled) (Quaestiones Disputatae: temas en debate, 2021)
Contemporary historiography and sociology have found contradictions between the devotion to certain Christian saints and the effective itinerary of life of each one of them. The historical data about John the Baptist and the cult that his devotees pay him show, in particular, the problem and the consequences derived from it for the faith of believers. If a general look at its worship in the Roman Catholic sphere of the last centuries allows us to detect the little relevant place that has been reserved for it, the Spanish-American environment is particularly useful for perceiving the remains of an almost mythical religiosity with respect to the Baptist, which favors yes cultural but does not attend to the incidences of the gospel in the various spheres of social life. Through an hermeneutic method searching for a critical view, the article retakes the mystical connotation of the forerunner of Jesus can contribute, in my opinion, to re-signifying his role in the Christian faith.